As condições de trabalho das assistentes sociais na proteção social básica em Paranaguá, Paraná - Lourenço, Carolina de Miranda Evangelista (2019)
The main theme of this research is the job of the social worker, with emphasis in the working conditions of these professionals in the basic social protection network of Paranaguá-PR. The research question that guided this investigation was: how are the working conditions of social workers employed in the public and private social assistance within the basic social protection network in the municipality of Paranaguá - PR? This guiding question had a central goal: to analyze the work conditions of social workers that work in public and private social assistance within the basic social protection network of the municipality of Paranaguá-PR, in view of the transformations led by contemporary capitalism, which is based in the productive restructuring of capital and neoliberalism. To address this proposal, specific goals were defined: to understand the constitution of social service as a job and as a profession within capitalism, as well as the influences of productive restructuring of capital in professional work; to comprehend how neoliberalism dictates State social policies and its historical implementation in Brazil; to analyze the repercussions of productive restructuring and neoliberalism in working conditions of social workers in public and private social assistance network, specifically in Paranaguá-PR. This research followed the dialectical method, which has as premise to present the concrete reality from its multiple determinations and contradictions, of a qualitative and field research standpoint. Among the adopted methodological procedures, we applied a semi-structured interview based on a questionnaire, using a recorder previously authorized by the interviewees and content analysis. The research aimed to contemplate the universe of eight social workers, however, it was possible to conduct the research with six social workers employed in public and private social assistance networks in the city. The results demonstrated that social workers are being submitted to precarious work conditions and needs such as physical space and working tools are not being guaranteed, reflecting in the workers' subjective conditions beyond their jobs.